GABAergic control of neurite outgrowth and remodeling during development and adult neurogenesis: general rules and differences in diverse systems - Sernagor, Evelyne; Chabrol, Francois; Bony, Guillaume; Cancedda, Laura (Frontiers in Cellular Neuroscience, 2010)
During development, GABAergic neurons mature at early stages, long before excitatory neurons. Conversely, GABA reuptake transporters become operative later than glutamate transporters. GABA is therefore not removed efficiently from the extracellular domain and it can exert significant paracrine effects. Hence, GABA-mediated activity is a prominent source of overall neural activity in developing CNS networks, while neurons extend dendrites and axons, and establish synaptic connections. One of the unique features of GABAergic functional plasticity is that in early development, activation of GABAA receptors results in depolarizing (mainly excitatory) responses and Ca2+ influx. Although there is strong evidence from several areas of the CNS that GABA plays a significant role in neurite growth not only during development but also during adult neurogenesis, surprisingly little effort has been made into putting all these observations into a common framework in an attempt to understand the general rules that regulate these basic and evolutionary well-conserved processes. In this review, we discuss the current knowledge in this important field. In order to decipher common, universal features and highlight differences between systems throughout development, we compare findings about dendritic proliferation and remodeling in different areas of the nervous system and species, and we also review recent evidence for a role in axonal elongation. In addition to early developmental aspects, we also consider the GABAergic role in dendritic growth during adult neurogenesis, extending our discussion to the roles played by GABA during dendritic proliferation in early developing networks versus adult, well established networks.